2023
DOI: 10.3389/fdgth.2022.970112
|View full text |Cite
|
Sign up to set email alerts
|

Virtual care and COVID-19: A survey study of adoption, satisfaction and continuing education preferences of healthcare providers in Newfoundland and Labrador, Canada

Abstract: IntroductionVirtual care has expanded during COVID-19 and enabled continued access to healthcare services. For many healthcare providers, the adoption of virtual care has been a new experience in the provision of healthcare services. The purpose of this survey study was to explore healthcare providers' experiences with virtual care during COVID-19.MethodsA web-based survey-questionnaire was developed by applying Rogers' theory of diffusion of innovation and distributed to healthcare providers (physicians, nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The Canadian Institute for Health Information (CIHI) reported that between March to September 2020, the percentage of patients availing of virtual care services increased from 6% to 56% [1]. Virtual care refers to the delivery of healthcare services digitally or at a distance using Information and Communications Technology [2,3,4]. During COVID-19 a variety of virtual care types were used with synchronous and asynchronous appointments being the most common [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Canadian Institute for Health Information (CIHI) reported that between March to September 2020, the percentage of patients availing of virtual care services increased from 6% to 56% [1]. Virtual care refers to the delivery of healthcare services digitally or at a distance using Information and Communications Technology [2,3,4]. During COVID-19 a variety of virtual care types were used with synchronous and asynchronous appointments being the most common [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual care refers to the delivery of healthcare services digitally or at a distance using Information and Communications Technology [2,3,4]. During COVID-19 a variety of virtual care types were used with synchronous and asynchronous appointments being the most common [3,4]. Synchronous virtual care refers to communication between healthcare provider and patient that occurs in real time and can include use of telephone and/or videoconferencing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations